A Tissue-Chopping Based Immunofluorescence Staining Method for Chloroplast Proteins - Wang, Lulu; Tang, Mingdong; Huang, Wenwen; An, Jinjie; Liu, Xiaomin; Gao, Hongbo (Frontiers in Plant Science, 2022)
Immunofluorescence staining is an important method for detecting the localization of proteins in the cell. It is also frequently used in the localization study of chloroplast-division proteins. Although this method has been improved before by using protoplasts, it still has some limitations. Now we developed a new method to make it much easier. We just broke the plant leaf tissue with a serrated blade, stained the samples directly, and simply lysed the tissue into separatable cells. The localization of the target protein can then be observed with a clear view. Since this method directly uses broken leaf pieces, it is very fast. It can also be applied to the plants in which protoplasts are difficult to prepare. We first used this method to observe the localization of a chloroplast division protein FtsZ1 in the wild-type Arabidopsis. A ring was clearly seen in the middle of chloroplasts. In addition, we used this method to analyze the localization of FtsZ1 in arc3 and pdv2 mutants, as well as in dozens of other species, including some woody plants. This new immunofluorescence staining method is not only easy to use, but also has a wide applicability in various plants.